Evaluation of group of Alpinia galanga n-hexane-Extract against Candida albicans by bioautography and thin layer chromatography - Eni Kusumaningtyas; Lusi Sukmawati; Estie Astuti (Jurnal Ilmu Ternak dan Veteriner, 2008)
Alpinia galanga has been used for centuries as a remedy for human diseases because it contains of therapeutic compounds. The objectives of this study was to define groups of the antifungal compounds of Alpinia galangal n-hexane-extract. Alpinia galanga was extracted by maceration method and the compounds were analyzed by phytochemical analysis. The extract was run on the thin layer chromatography (TLC) plate silica gel GF254 with dichloromethane and toluene. Bioautography was conducted to determine antifungal compounds against Candida albicans. Active compounds on the previous step were identified by running extract on TLC plate and sprayed with Vanilin sulphuric acid and Liebermann-Burchard I. The results of phytochemical analysis showed that Alpinia galanga n-hexane-extract contains alkaloids, flavonoids, saponins, triterpenoid, tannins and aromatic oil. Bioautogram revealed that there was one inhibition zone against Candida albicans. The active compounds in the inhibition zone were in Rf value 0.75 and 0.89. One out of the two compounds was identified as a compound from terpenoid group.     Key Words: Compound, Extract, Alpinia galanga, Candida albicans